PEMBACAAN DEKONSTRUKSI CERPEN "ZINA" KARYA PUTU WIJAYA - Ronidin Ronidin (Puitika)
This article is aimed at revealing the paradox meaning of some events in short story “Zina” written by Putu Wijaya. The short story “Zina” is chosen to be analyzed because it describes some unique events in the short story and they are beyond of common logic. The analysis of this short story is conducted by using deconstruction approach. It is a qualitative research and it is described descriptively. Based on the result of the analysis, it is found that the unique events that are found in short story “Zina” which seems paradox with common sense, in fact there is a truth inside. A wife who ask permission to her husband to have an affair with somebody else, a forbidden affair that is done in front of palace and bus way line, and an open affair in front of public are unique events that hide many paradox meanings. Some of paradox meanings are; the importance of husband’s admittance for a wife, the importance of new atmospheres in a family, and the importance of governing social awareness.